ANDROGEN DEFICIENCY ASSOCIATES WITH INCREASED ADVANCED GLYCATED END PRODUCTS, GALECTIN-3 IN HYPERTENSIVE MEN WITH BENIGN PROSTATIC HYPERPLASIA. (June 2022) - Sirenko, Oksana; Kuryata, Olexandr
Abstract : Objective: The aim of the study was to estimate the interaction between testosterone level with advanced glycation end products, galectin-3 in hypertensive men. Design and method: The study included 38 men with hypertension and benign prostatic hyperplasia. Advanced glycation end products, matrix metalloproteinases-9 activ¬ity, galectin-3, C-reactive protein, testosterone level were determined in all of patients. The 1st group was made up of men with hypertension and benign prostatic hyperplasia with testosterone deficiency; 2nd group – of men without testosterone deficiency. Results: Men with hypertension and benign prostatic hyperplasia with testosterone deficiency had a significantly higher level of advanced glycation end products, galectin-3 (p < 0.001). The presence of androgen deficiency in hypertensive men with benign prostatic hyperplasia was associated with increased levels of advanced glycation end products (OR = 2.8, p < 0.001), galectin-3 (OR = 2.2, p < 0.001). Conclusions: testosterone deficiency in hypertensive men with benign prostatic hyperplasia is associated with increased serum advanced glycation end products, galectin-3.